Bromotrimethylsilane as a selective reagent for the synthesis of bromohydrins. Issue 24 (16th April 2021) - Giomi, Donatella; Salvini, Antonella; Ceccarelli, Jacopo; Brandi, Alberto
Abstract : Glycerol, a by-product of biodiesel production, can be efficiently converted into α-monobromohydrin or α, γ-dibromohydrin with trimethylsilyl bromide (TMSBr), in solvent-free and mild reaction conditions. Abstract : Bromotrimethylsilane (TMSBr) is a very efficient reagent in the solvent-free conversion of glycerol into bromohydrins, useful intermediates in the production of fine chemicals. As glycerol is a relevant by-product in biodiesel production, TMSBr has been also tested as a mediator in transesterification in acidic conditions, providing FAME from castor oil in good yields, along with bromohydrins from glycerol. Subsequently the glycerol conversion was optimized and depending on the reaction conditions, glycerol can be selectively converted into α-monobromohydrin (1-MBH) or α, γ-dibromohydrin (1, 3-DBH) in very good yields.